Use of on-line evidence databases by Australian public health practitioners. - Adily, Armita
To investigate use of a web-based portal, known as the Clinical Information Access Program (CIAP), and evidence databases in an Australian population health workforce. Self-administered postal survey of 104 staff in a regional Division of Population Health in Sydney, Australia. The main outcome measures were CIAP use and organization support for CIAP use. Two thirds of the respondents agreed that using CIAP was a legitimate part of their practice. However, half agreed that staff were encouraged to use it. One in five respondents (21%) used CIAP weekly. CIAP use was significantly associated with medical qualification or, among non-medical staff, with having at least a Masters qualification. CIAP use was not associated with occupational category, gender, age, employment status nor years of experience. Use of specific evidence databases such as Cochrane also differed significantly by respondents' characteristics. There has been only partial uptake of on-line databases among this population health workforce, particularly according to attainment of relevant postgraduate qualifications. As CIAP is a resouce for evidence-based practice, greater effort to increase its use is recommended to ensure population health does not fall behind hospital-based clinicians.
Keywords: Evidence-based practice; Evidence resources